KOEFISIEN PINDAH PANAS KESELURUHAN ALAT PENUKAR PANAS DALAM PENDINGINAN NOKTURNAL - Gunadnya, I.B.P.; Abdullah, K.; Tambunan, A.H.; Purwanto, Y.A.; Oktaufik, M.A.M. (Agrotekno, 2012)
A series of field experiments have been conducted to estimate values of thermal parameters of a heat exchanger, such as overall heat transfer coefficient (U), number of transfer units (NTU), and effectiveness (?), in a nocturnal cooling system. Accumulated experimental data showed that these parameters are proportional to the logarithmic relation to mass flow rate of water flowing into the heat exchanger. Empirical correlation developed for this purpose indicated that correlation coefficient of U was 0.76. the correlation function developed for cross-flow is applicable to predict outlet air temperature with an average error of 0.10C.
Keywords: heat transfer, overall heat transfer coefficient, correlation function, NTU, heat exchanger affectivity, nocturnal cooling